Elevating Married Adolescents' Voices for Responsive Reproductive Healthcare in Syria - Chowdhary, Pari; Kalyanpur, Anushka; Mekuria, Feven Tassaw; Altinci, Ihlas (Frontiers in Reproductive Health, 2022)
Increases in early marriage and pregnancy resulting from Syria’s humanitarian crisis highlight a critical gap in adolescents’ access to life-saving sexual and reproductive health information and services, and a larger need for adolescent-specific interventions grounded in gender transformative approaches. Seeking to address this, CARE, UNFPA and Syria Relief & Development adapted global evidence-based approaches to humanitarian contexts to create the Adolescent Mothers Against all Odds (AMAL) Initiative for pregnant girls and first-time mothers aged 10 to 18 years. Designed to improve the lives of young girls through responsive health systems and enabling environments, AMAL includes three components: a Young Mothers Club for first-time mothers and pregnant girls, participatory dialogues with health providers, and reflective dialogues with girls’ marital family and community members. The AMAL Initiative intends to ensure responsiveness to the unique vulnerabilities of adolescent sub-groups by co-implementing with them. Select girls undergo additional leadership training and serve as adolescent representatives on community advisory groups sharing feedback for program improvement. 104 first-time mothers and pregnant girls, 219 community members, and 120 health providers participated in AMAL in northwest Syria. In a mixed methods evaluation, facilitators administered monitoring tools to identify program improvements, pre-post surveys to assess outcomes, and end-line discussions to gather perceptions of impact. Girls reported a 47% overall increase in self-esteem, confidence, health-seeking capacity, and communication ability. Community support for girls’ use of family planning increased by 27% and girls’ equal access to services by 35%. Findings across all participant groups demonstrate decreased expectations of early marriage and increased acceptance of family planning post-marriage. Areas that participants cited for potential improvement included programming for girls/women above the age of 18 years, and additional training for health providers on long-acting contraceptive methods. These results show that participatory adolescent-centered sexual and reproductive health programming is not only feasible in crisis settings but can improve the self-efficacy of vulnerable adolescents to overcome barriers to accessing healthcare and improving well-being. The AMAL Initiative is now being scaled up through local partners in Syria and piloted in northern Nigeria.